2007
DOI: 10.1590/s0074-02762007005000056
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Aedes aegypti(Diptera: Culicidae) container productivity in a slum and a suburban district of Rio de Janeiro during dry and wet seasons

Abstract: Seasonal variation in container productivity and infestation levels by

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
102
1
7

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 132 publications
(131 citation statements)
references
References 14 publications
16
102
1
7
Order By: Relevance
“…Different situations have been described for other regions of Brazil. In the southeast, the flasks and drains groups were most commonly found to have immature forms of the vector in domiciles in the City of São Paulo, and a similar result was noted for the grease traps in the City of Rio de Janeiro 24,25 . Another study carried out in the north, in Manaus, Amazonas, found that the flasks and tires groups accounted for the largest number of larvae and pupae 17 .…”
Section: Discussionsupporting
confidence: 62%
“…Different situations have been described for other regions of Brazil. In the southeast, the flasks and drains groups were most commonly found to have immature forms of the vector in domiciles in the City of São Paulo, and a similar result was noted for the grease traps in the City of Rio de Janeiro 24,25 . Another study carried out in the north, in Manaus, Amazonas, found that the flasks and tires groups accounted for the largest number of larvae and pupae 17 .…”
Section: Discussionsupporting
confidence: 62%
“…We fit both models to our data, using linear and nonlinear least squares standard procedures available in the software R 2.2.0 (R Development Core Team, http://www.R-proj ect.org). From the lower and upper 95% limits of the confidence interval for PDS (estimated by the nonlinear model), we derived two quantities: the average life expectancy, defined as 1/-loge PDS 22 , and longevity, defined as PDS 10 , where 10 is the duration of the extrinsic incubation period for dengue virus, when more than 76% of orally experimentally infected mosquitoes have the virus in the salivary glands 23 . Susceptible mosquitoes that survive in the field for 10 or more days after an infected blood meal are expected to live long enough to transmit the dengue virus.…”
Section: Estimation Of Daily Survival Ratesmentioning
confidence: 99%
“…It generally breeds in large artificial containers, has high daily survival rates, and moves across variable distances depending on the environment and climate, while its populations are highly genetically structured 3,4,5,6,7,8 . Differences in the degree of urbanization and in socio-economic status between adjacent blocks mean that Rio de Janeiro is a mosaic in terms of dengue epidemiology, where specific control activities for each area might be required 4,9,10 . Variations in the mosquito population size, daily survival rates, biting rates, and the duration of the extrinsic incubation period and/or dengue virus susceptibility within neighborhoods might elicit differential vectorial capacity, and consequently differences in disease transmission dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, Aedes aegypti is an urban mosquito that makes use of available infrastructure for its reproduction (32,33).…”
Section: Discussionmentioning
confidence: 99%